2020
DOI: 10.1111/tpj.14720
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of phospholipase Dδ family in tobacco pollen tubes

Abstract: Phosphatidic acid (PA), important signalling and metabolic phospholipid, is predominantly localized in the subapical plasma membrane (PM) of growing pollen tubes. PA can be produced from structural phospholipids by phospholipase D (PLD) but the isoforms responsible for production of plasma membrane PA were not identified yet and their functional roles remain unknown. Following genome-wide bioinformatic analysis of PLD family in tobacco, we focused on the pollen-overrepresented PLDδ class. Combining live-cell i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…PA has a specific pattern of intracellular localization. Under basal conditions, PA has been detected in the plasma membrane (PM) in various plant objects: growing tobacco pollen tubes [ 41 , 42 ], mature trichomes [ 43 ], epidermal and meristematic root cells and shoot tissues [ 44 ]. However, PA has also been detected in cell membranes other than PM.…”
Section: Spatiotemporal Characteristics Of Phosphatidic Acid As a Sig...mentioning
confidence: 99%
See 1 more Smart Citation
“…PA has a specific pattern of intracellular localization. Under basal conditions, PA has been detected in the plasma membrane (PM) in various plant objects: growing tobacco pollen tubes [ 41 , 42 ], mature trichomes [ 43 ], epidermal and meristematic root cells and shoot tissues [ 44 ]. However, PA has also been detected in cell membranes other than PM.…”
Section: Spatiotemporal Characteristics Of Phosphatidic Acid As a Sig...mentioning
confidence: 99%
“…A recent study on the functions of PLDδ-family phospholipase in tobacco showed that pollen tubes support a high level of expression of PLDδ genes during growth. For some of the PLDδ isoforms, the unique localization was detected, and the sequences important for binding to the PM were determined [ 42 ]. It has been noted that the increased level of PA, formed by the overexpression of Nt PLDδ3 isoform, causes specific morphological phenotypes indicating a violation of the balance of vesicular traffic and membrane recirculation [ 42 ].…”
Section: Effect Of Pa On Membrane Statusmentioning
confidence: 99%
“…Interestingly, ROS-production by NtNOX itself is in part regulated by PLD-produced PA [62]. Recently, bioinformatic analysis of tobacco PLDδs classified five different NTPLDδs, NtPLDδ1 to 5 [276]. Overexpression of these PLDs in tobacco pollen tubes showed preferential cytosolic localisation for NtPLDδ1 and 2, plasma membrane localisation for NtPLDδ4 and 5, and an equilibrium between both compartments for NtPLDδ3.…”
Section: Phospholipase D-produced Phosphatidic Acid Regulates Pollen Tube Growthmentioning
confidence: 99%
“…Tobacco pollen tubes overexpressing NtPLDδ3 showed the most severe phenotypes, including apical membrane invaginations. Due to the observed phenotypes, a role for NtPLDδ3 in membrane trafficking was proposed, highlighting the importance of lipid-mediated signalling for the maintenance of secretion in physiological tip growth [276].…”
Section: Phospholipase D-produced Phosphatidic Acid Regulates Pollen Tube Growthmentioning
confidence: 99%
“…Among good candidates for mechanotransduction is plant-specific phospholipase D delta (PLDδ) (Ho et al 2009 ; Cvrčkova 2013 ; Pleskot et al 2013 ; Pejchar et al 2020 ), a possible mediator in the cell wall–PM-cytoskeleton continuum (Marc et al 1996 ; Gardiner et al 2003 ) and also able to regulate the activity of both MTs and AFs (Petrasek and Schwarzerova 2009 ). In particular, PLDδ binds to plant flotillin homolog (Ho et al 2009 ), a lipid microdomain marker (Martin et al 2005 ), constituting the sites where multimolecular signaling complexes containing G-proteins or kinases, flotillin, PLDδ, MTs, actin filaments, Hsp70 and others are assembled and take part in cell signaling and vesicle trafficking (Martin et al 2005 ; Ho et al 2009 ; Tapken and Murphy 2015 ).…”
Section: Introductionmentioning
confidence: 99%